Analisis faktor-faktor yang mempengaruhi nasabah dalam memilih Bank Syariah - Rizalianto, Robur AD; Anwar, Saiful (ARKA INSTITUTE, 2023)
The market share of Islamic banking in Banten is still below 6.65 percent compared to conventional banks. The purpose of this study is to determine what factors influence people in determining financial institutions for their banking activities. The variables used are service quality, promotion, knowledge, motivation, religiosity and information technology. This study was conducted in Banten Province in June 2023 with a sample of 100 respondents. Quantitative data processing will be processed with AMOS 22 software. This study is useful for providing input to Islamic banks in making good plans so that customers become loyal to Islamic banks. The results of the study showed that the service quality variable was significant while the motivation, knowledge, religiosity, promotion and information technology variables were not significant. It can be concluded that in the variables studied, only service quality influenced customer selection of banks.